Depiction of a Surasundari as female bracket above the pillar capital - Temples of India Project Team (Jio Institute, 2024)
The central pillars of the mandapa (pillared hall) in the Neelkanth Mahadev Temple have depictions of surasundaris (celestial damsels) as female bracket figures above the pillar capitals. These figures are on all four corners of the ceiling. The female figures are carved in a different stone than the pillars, lintels, and walls of the temple interiors.